2016
DOI: 10.13075/mp.5893.00317
|View full text |Cite
|
Sign up to set email alerts
|

Papain-induced occupational rhinoconjunctivitis and asthma – A case report

Abstract: This report presents a case of occupational asthma, rhinitis and conjunctivitis to papain in a 50-year-old herbs and spices packer, with documented increased eosinophilia in induced sputum and in the nasal lavage fluids after a specific inhalation challenge test (SICT) and specific nasal challenge test (SNCT) with this enzyme. Immunoglobulin E-mediated (IgE) sensitization to papain was confirmed by positive results of a skin prick test with specific solution. Specific inhalation and nasal challenge tests demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Data about the gastrointestinal resistance of the pollen and mite PLCPs are not available. In reality, in addition to food proteins, every protein known as inhaled allergen can also be ingested ( Figure 2 ) and vice versa—some food allergenic proteins ( Figure 1 ) can be inhaled [ 35 , 59 , 60 ]. For instance, it is possible for pollen allergens to be ingested in foods such as honey or in periods of pollination [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Resistance To Gastrointestinal Digestionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data about the gastrointestinal resistance of the pollen and mite PLCPs are not available. In reality, in addition to food proteins, every protein known as inhaled allergen can also be ingested ( Figure 2 ) and vice versa—some food allergenic proteins ( Figure 1 ) can be inhaled [ 35 , 59 , 60 ]. For instance, it is possible for pollen allergens to be ingested in foods such as honey or in periods of pollination [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Resistance To Gastrointestinal Digestionmentioning
confidence: 99%
“…Outside those geographical areas sensitisation to papaya does not usually occur from eating papaya fruit. In fact, rhinitis and asthma are reported to affect only workers of industries where papaya is handled [ 35 , 126 , 127 , 128 ]. A single case was reported many years ago [ 129 ] of a patient experiencing severe systemic allergic reaction after the ingestion of meat tenderiser.…”
Section: Sources Of Plcps Known For Allergenicity And/or Ige Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between control populations showed that Foxa2 is ~6-fold more highly expressed in lung epithelial cells than in lung T-cells (Figure S3A). To induce AAD, we used papain as allergen, which induces allergic airway inflammation by initiating a Th2 immune response and is linked to occupational and non-occupational asthma and allergy in humans (29,35,(39)(40)(41)(42)(43)(44)(45). We administered intranasal papain in PBS to Foxa2cKO (Foxa2f/fCD4Cre+) and control (Foxa2f/ fCD4Cre neg ) mice on day 0 and day 7 and sacrificed mice on day 10, treating with PBS alone at the same time points as negative control (Figure S1A).…”
Section: Conditional Deletion Of Foxa2 From T-cells Increases Inflamm...mentioning
confidence: 99%
“…PLCPs can cause occupational allergic reactions due to exposure to airborne particles, as reported, for instance, for papain [11,31] or bromelain [32]. The same allergens can cause nonoccupational reactions due to the ingestion of foods containing the allergenic protein [33].…”
Section: Introductionmentioning
confidence: 96%